Effect of oil prices to the emerging stock market in Middle East (Bahrain, Jordan, Kuwait and Qatar) / Safina Ahmad - Ahmad, Safina (2010)
Oil has played a critical role to shape countries development since effect of oil prices on a country’s economy has been and continuous to be keen interest from many people particularly economist. Oil is the main product in the most of Middle East countries especially in the GCC country such as Bahrain, Kuwait, Oman and Qatar. This study is focusing and elaborate more on the effect oil prices to stock market in the focusing countries namely Bahrain, Jordan, Qatar and Kuwait where this dependent countries are mostly depend on the oil. The weekly closing price of stock index in 5 years period of study from 1st January 2005 until 31st December 2009 were collected and the finding reveal that these four countries (Bahrain,Kuwait,Jordan and Qatar) statistically showing significant positive relationship between Oil Price to stock market. Furthermore the second results, shows that the current market return for each market were positively affected by the previous market return.